Kontaktni kras v Kočevskem Rogu in Kočevski Mali gori - Gostinčar, Petra (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
On high Dinaric karst plateaus of Kočevski Rog and Kočevska Mala gora, the so-called contact karst is present. Geomorphic processes and landforms of four case study areas of contact karst were researched in detail. Two types of contact karst were recognized: between non-carbonate and carbonate rocks and between different carbonate rocks. In the first case, ponors and blind valleys (active and fossil) were formed and concave forms near the contact are infilled with non-carbonate sediments. On the contact between different carbonate rocks (dolomite and limestone), the forms are similar but less evident, e.g. ponors (active and fossil), ponor steepheads and dry valleys.
Keywords: contact karst; geomorfologija; geomorphology; karstology; Kočevski Rog; kontaktni kras; kras (geologija); krasoslovje; Slovenia; Slovenija